The relationship between physical activity and the risk of type 2 diabetes mellitus in Ellisras rural young adults aged 22 to 20 years : Ellisras longitudinal study - Matshipi, Moloko (My University, 2019)
Background Type 2 diabetes mellitus (T2DM) is an increasing challenge globally, and is estimated to affect 439 million adults by 2030. This estimate is linked to an unhealthy lifestyle with characteristics such as low physical activity (PA) and high plasma glucose levels (PGLs). Studies associating PA with insulin resistance and diabetes among adults and adolescents have been conducted widely in developed countries. Such studies are scanty among rural populations, especially in Africa. Assessment of the burden of diabetes and associated lifestyle risk factors in developing countries is essential in order to encourage appropriate intervention strategies to counter the increasing prevalence. Aim and objectives The aim of this study was to investigate the relationship between PA and T2DM among rural young adults aged 22 to 30 years in Ellisras area in Limpopo Province, South Africa Methods A total of 713 young adults (349 males and 364 females) who have been part of the Ellisras Longitudinal Study participated in the current study. Physical activity data was collected using a validated questionnaire. After an overnight fast, participants provided fasting venous blood samples for determination of plasma glucose and insulin. Insulin resistance was estimated using the homeostasis model assessment of insulin resistance. Anthropometric measurements (waist circumference and height) were performed using standard procedures. Linear and logistic regressions were used to assess the relationship between PA, pre-diabetes, insulin resistance and T2DM; and the odds of having T2DM with low PA levels. Results The prevalence of physical inactivity was 67.3 and 71.0% for males and females, respectively. That of pre-diabetes was between 45.7% and 50.2%. The prevalence of diabetes was 9.6% for males and 10.1% for females while for insulin resistance was 22.9% for males and 29.3% for females. Linear regression found a significant relationship (p<0.05) between physical activity and blood glucose (ß =5.715; 95% CI 4.545; 6.885), waist circumference (ß = 37.572; 95% CI 25.970; 49.174) and waist-toheight ratio (ß = 0.192; 95% CI 0.087; 0.296). Logistic regression found a significant (p<0.05) relationship between low physical activity and T2DM (Odds ratio = 2.890; 95% CI 1.715; 4.870) and insulin resistance (Odds ratio = 1.819; 95% CI 1.266; 2.614). Conclusion Physical activity is low in this population, and is independently associated with T2DM and insulin resistance. KEY WORDS Type 2 diabetes mellitus; pre-diabetes; insulin resistance; physical activity; young adults; rural South African population.
Thesis (M.Sc. (Physiology)) -- University of Limpopo, 2019
Keywords: Type 2 diabetes mellitus; Pre-diabetes; Insulin resistance; Physical activity; Young adults; Rural South African population; Diabetes